2020
DOI: 10.3389/fncel.2020.00072
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking Mechanisms of Synaptic Dysfunction in Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease characterized by progressive memory loss. Although AD neuropathological hallmarks are extracellular amyloid plaques and intracellular tau tangles, the best correlate of disease progression is synapse loss. What causes synapse loss has been the focus of several researchers in the AD field. Synapses become dysfunctional before plaques and tangles form. Studies based on early-onset familial AD (eFAD) models have supported that synaptic transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 238 publications
(291 reference statements)
0
37
0
Order By: Relevance
“…In the context of a behaving animal, we speculate that this abnormality may culminate as imbalanced neural circuits. This imbalance may eventually lead to neuronal hyperactivity and feedforward production, then subsequent accumulation of Ab before, in parallel, or in concert with previously reported postsynaptic effects (Palop and Mucke, 2016;Perdigã o et al, 2020;Sheng et al, 2012).…”
Section: Articlementioning
confidence: 78%
See 1 more Smart Citation
“…In the context of a behaving animal, we speculate that this abnormality may culminate as imbalanced neural circuits. This imbalance may eventually lead to neuronal hyperactivity and feedforward production, then subsequent accumulation of Ab before, in parallel, or in concert with previously reported postsynaptic effects (Palop and Mucke, 2016;Perdigã o et al, 2020;Sheng et al, 2012).…”
Section: Articlementioning
confidence: 78%
“…The SVC is at the core of the presynaptic terminal and SNARE proteins are among the most impaired proteins in our datasets. The vast majority of previous evidence points to the postsynaptic membrane as the primary site of Ab synaptic toxicity (DeBoer et al, 2014;Perdigã o et al, 2020;Serrano-Pozo et al, 2011;Sheng et al, 2012). However, the localization and processing of APP mainly occurs at presynaptic terminals, and it is not without precedence to find that APP interacts with SVs (Masliah et al, 1994a;Oddo et al, 2003).…”
Section: Articlementioning
confidence: 99%
“…Several supporting lines of evidence implicate dysregulation of endocytosis and presynaptic endocytic proteins in AD thus supporting why normalization of this process reduces amyloidogenic APP processing and ultimately Aβ 42 production. Much of the previous evidence gathered on Aβ toxicity implicates the postsynaptic membrane as the primary site (DeBoer et al, 2014; Perdigão et al, 2020; Serrano-Pozo et al, 2011; Sheng et al, 2012). However, the localization and processing of APP mainly occurs at presynaptic terminals, and it has been previously shown that APP interacts with SVs (Masliah et al, 1994a; Oddo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In general, axonal and dendritic swelling are probably suggestive of impaired intraneuronal trafficking. Intracellular sorting and transportation of macro- and micro-molecules between the somata, dendrites, and axons are vital for the anatomical and physiological hemostasis of neurons, which are dependent on complex cellular and molecular interplays that require extensive investigations in the future (Stokin et al, 2005 ; Kimura and Yanagisawa, 2018 ; Perdigão et al, 2020 ). During intraneuronal tangle formation, pTau is disengaged from the microtubules and redistributed from the axon to the soma and dendrites (Hall and Yao, 2000 ; Spires-Jones et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%